Analisis Framing Model Robert N Entmant Mengenai Pemberitaan Tenaga Honorer Diangkat Menjadi Pns Pada Media Daring Cnbc Indonesia dan Detik.com - Regita Indah Cahyani; Hendra Setiawan (Peneliti.net, 2023)
CNBC Indonesia and detik.com are online news portals that deliver factual and actual news to the public. The Bill on Amendments to Law Number 5 of 2014 concerning the State Civil Apparatus is one of the news items presented by the two media. This studies uses a qualitative methods with a qualitative descriptive approach. And aims to understand the framing of the two media regarding the news with the Robert N Entman framing model. The records collection technique is documentation from the web portals of the two media. The results of applying Robert N Entmant's framing analysis model can be decided by deciding on troubles and emphasizing or highlighting sure factors of the complicated and diverse truth of records. From this analysis, it changed into found that there had been differences in points, define problems, diagnose causes, make moral judgments, and treatment recommendations. CNBC media described the news as good news by highlighting the benefits received by civil servants. Meanwhile, detik.com media described the news from their point of view by highlighting the statement by the Minister of PAN-RAB Abdullah Azwar Anas regarding the impact of implementing the bill.